From Josephus to Yosippon and Beyond : Text - Re-interpretations - Afterlives - Avioz, Michael,; Bay, Carson,; Henten, Jan Willem van, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
Two millennia ago, the Jewish priest-turned-general Flavius Josephus, captured by the emperor Vespasian in the middle of the Roman-Jewish War (66-70 CE), spent the last several decades of his life in Rome writing several historiographical works in Greek. Josephus was eagerly read and used by Christian thinkers, but eventually his writings became the basis for the early-10th century Hebrew text called Sefer Yosippon, reintegrating Josephus into the Jewish tradition. This volume marks the first edited collection to be dedicated to the study of Josephus, Yosippon, and their reception histories. Consisting of critical inquiries into one or both of these texts and their afterlives, the essays in this volume pave the way for future research on the Josephan tradition in Greek, Latin, Hebrew, and beyond.